James O. Crosby, The text tradition of the Memorial "Católica, sacra, real magestad". University of Kansas Press, Lawrence, Kansas, 1958; [xiii] + 8i pp. - Mas, Amédée (El Colegio de México, 1959)
Se reseñó el libro: The text tradition of the Memorial "Católica, sacra, real magestad".